Motor strategy in rapid sequential swallowing: new insights. - Chi-Fishman, Gloria; Sonies, Barbara C. (Journal of Speech, Language & Hearing Research, 2000)
This study examined the physiological properties and movement strategies of normal, rapid sequential swallowing during simultaneous videofluoroscopy (VFS) and submental surface electromyography (EMG). Ten subjects performed discrete (5 and 15 cc) and sequential (150 cc in tilted and upright head postures) swallowing tasks. Analyses included VFS event timing, movement/bolus passage characteristics, EMG amplitude waveforms, and peak and offset EMG amplitudes. Results revealed that sequential swallows were significantly shorter than discrete swallows in several VFS event durations, but significantly longer in pharyngeal transit and stage transition times. The hyolaryngeal system exhibited a cyclical IDdrise and partial fallIDD movement pattern during sequential swallows on VFS, corresponding to a repetitive IDdactivation and partial deactivationIDD characteristic on EMG. Greater peak EMG amplitude for sequential than discrete swallows was found in 6/10 subjects. Pharyngeal bolus merging, preparatory laryngeal gestures, and penetration without aspiration were also observed in some subjects on VFS. Intersubject differences were significant in timing measures and EMG amplitude. Our findings of individual variability and subject-specific strategies for task accommodation support the notion of built-in plasticity in the deglutitive motor complex. Reprinted by permission of the publisher. Reprinted by permission of the publisher.